How industry and occupational stereotypes shape consumers' trust, value and loyalty judgments concerning service brands. (5th October 2021) - Gidaković, Petar; Zabkar, Vesna
Abstract : Purpose: Longitudinal studies have shown that consumer satisfaction has increased over the last 15 years, whereas trust and loyalty have decreased during the same period. This finding contradicts the trust–value–loyalty model (TVLM), which posits that higher satisfaction increases consumers' trust, value and loyalty levels. To explain this counterintuitive trend, this study draws on models of trust formation to integrate the stereotype content model and the TVLM. It argues that consumers' occupational and industry stereotypes influence their trust, value and loyalty judgments through their trusting beliefs regarding frontline employees and management practices/policies. Design/methodology/approach: The study was conducted among 476 consumers who were randomly assigned to one of five service industries (apparel retail, airlines, hotels, health insurance or telecommunications services) and asked to rate their current service provider from that industry. Findings: The results suggest that both occupational and industry stereotypes influence consumers' trusting beliefs and trust judgments, although only the effects of industry stereotypes are transferred to consumers' loyalty judgments. Research limitations/implications: The results of the study indicate that industry stereotypes have become increasingly negative over the last decades, which has a dampening effect on the positive effects of satisfaction. Practical implications: This study provides guidelines for practitioners regarding the management of frontline employees and the development of consumer trust, value and loyalty. Originality/value: This is the first study to propose and test an explanation for the counterintuitive trend concerning customer satisfaction, trust and loyalty. It is also the first to examine the roles of multiple stereotypes in the relationship between consumers and service providers.